2022
DOI: 10.3390/jcm11061733
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Somatic Vulnerability, Psychosocial Robustness and Injury-Related Factors on Fatigue following Traumatic Brain Injury—A Cross-Sectional Study

Abstract: Fatigue is a common symptom after traumatic brain injuries (TBI) and a crucial target of rehabilitation. The subjective and multifactorial nature of fatigue necessitates a biopsychosocial approach in understanding the mechanisms involved in its development. The aim of this study is to provide a comprehensive exploration of factors relevant to identification and rehabilitation of fatigue following TBI. Ninety-six patients with TBI and confirmed intracranial injuries were assessed on average 200 days post-injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 75 publications
3
8
0
Order By: Relevance
“…In a previous cross-sectional analysis of the first wave (6 months post-injury) of the current study, 15 we found 3 factors underlying biopsychosocial correlates of fatigue. Pain, somatic symptoms, daytime sleepiness, and insomnia were related to fatigue through a factor termed "somatic vulnerability."…”
Section: E245supporting
confidence: 45%
See 4 more Smart Citations
“…In a previous cross-sectional analysis of the first wave (6 months post-injury) of the current study, 15 we found 3 factors underlying biopsychosocial correlates of fatigue. Pain, somatic symptoms, daytime sleepiness, and insomnia were related to fatigue through a factor termed "somatic vulnerability."…”
Section: E245supporting
confidence: 45%
“…In a previous cross-sectional analysis of the first wave (6 months post-injury) of the current study,15 we found 3 factors underlying biopsychosocial correlates of fatigue. Pain, somatic symptoms, daytime sleepiness, and insomnia were related to fatigue through a factor termed “somatic vulnerability.” Psychological distress, personality traits (neuroticism, extraversion, conscientiousness, and optimism), behavioral inhibition, and loneliness were associated with fatigue through a factor termed “psychosocial robustness.” Third, we demonstrated injury severity and neuropsychological variables to be associated with fatigue, although the effects were small.…”
supporting
confidence: 45%
See 3 more Smart Citations